Defence Diplomacy and the Deepening of Indonesia-Türkiye Defence Cooperation: Evidence from the KAAN Fighter Jet Procurement - Diphda, Bintang Corvi; Wiswayana, Wishnu Mahendra (Teunuleh Publisher, 2026)
This article examines how the KAAN fighter jet procurement deepened defense relations between Indonesia and Türkiye through defense diplomacy. Using Lech Drab’s framework of defense diplomacy, the article argues that the KAAN case should be understood not merely as a procurement decision, but as a form of strategic engagement that elevated bilateral defense relations to a more intensive and institutionalized level. Methodologically, the study applies a qualitative single case study design, with data collected through a structured desk review of official statements, policy documents, company releases, academic works, and reputable news reports, and analyzed through thematic analysis. The findings show that the KAAN procurement deepened Indonesia-Türkiye defense relations through three connected mechanisms: the strengthening of strategic trust, the expansion of defense-industrial cooperation, and the enhancement of Indonesia’s defense capability. More broadly, the article finds that Indonesia’s cooperation with Türkiye reflects an effort to build a stable long-term defense relationship that can widen Indonesia’s strategic influence while preserving its autonomy amid great-power competition. The case also confirms that defense diplomacy remains a practical means through which middle powers can simultaneously build confidence, strengthen military capability, and develop the defense industry. In this sense, the KAAN case demonstrates the growing sophistication of defense diplomacy among middle powers. Lastly, this study is limited to a single qualitative case and does not assess the long-term operational outcomes of the KAAN program or compare it systematically with Indonesia’s other procurement pathways.